2010
DOI: 10.1002/da.20739
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and the lifetime risk of generalized anxiety disorder

Abstract: Background-Anxiety disorders are thought to have their origins in early childhood, though they have not yet been studied as a potential outcome of impaired fetal growth, which has been implicated in the developmental etiologies of many psychopathologies. This study investigated the association between indicators of fetal growth and the development of generalized anxiety disorder (GAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 57 publications
(102 reference statements)
1
27
0
Order By: Relevance
“…21 The occurrence of low birth weight and preterm birth has also been found to be a risk factor in itself for the development of GAD in later years. 22 Several studies have shown a link between stress in utero and adverse neurobehavioral outcomes in the neonatal period. This correlation has been proposed to be a result of dysregulation of the hypothalamic-pituitary axis of the mother and the offspring.…”
Section: Consequences Of Gad In Mother and Infantmentioning
confidence: 99%
“…21 The occurrence of low birth weight and preterm birth has also been found to be a risk factor in itself for the development of GAD in later years. 22 Several studies have shown a link between stress in utero and adverse neurobehavioral outcomes in the neonatal period. This correlation has been proposed to be a result of dysregulation of the hypothalamic-pituitary axis of the mother and the offspring.…”
Section: Consequences Of Gad In Mother and Infantmentioning
confidence: 99%
“…In another study, birth weight z-scores were divided into groups by quintiles and it was found that those in the lowest and highest quintile groups were at higher risk of anxious and depressive symptoms (115). Lastly, one study found high birth weight (>3.5 kg) was protective of GAD diagnosis, but no difference in risk between normal and low birth weight (<2.5 kg) (113). Conversely, three studies which divided birth weight into three, four or seven categories (107,112,133) found linear trends with better outcomes at higher weights.…”
Section: Non-linear Associations In Epidemiological Studiesmentioning
confidence: 99%
“…Epidemiological studies testing the association between various measures of birth weight with later psychopathology have found associations with symptoms of distress (103)(104)(105), depression (106)(107)(108)(109)(110)(111) and/or anxiety (112,113), stress susceptibility (114), depressive and anxious symptoms (115)(116)(117)(118) and psychiatric morbidity (119), which in some cases were found in females only (108,110,116,117). A number of studies which used alternative birth dimensions found associations between higher ponderal index and lifetime depression in women (109), smaller birth length adjusted for gestational length (GA) and child behavioural problems (120), and shorter GA and depression (105).…”
Section: Prenatal Risk Factors For Later Psychopathology Fetal Develomentioning
confidence: 99%
See 2 more Smart Citations